2009
DOI: 10.1590/s1807-59322009000100009
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Multimorbidity of Elderly Outpatients

Abstract: INTRODUCTION: Substantial medical research has established an inverse relationship between quality of life and illness. However, there exists minimal evidence for such a connection in the context of stable and controlled diseases. OBJECTIVE: We wished to correlate multimorbidity with quality of life for elderly patients who suffer from stable chronic diseases. METHODS: We used a tool to evaluate quality of life, namely World Health Organization quality of lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
2
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 30 publications
3
22
2
13
Order By: Relevance
“…23 The number of medicines negatively influences the Environmental and Physical domains of the studied elderly's QoL and GQoL. These findings are similar to the study 22 in which a negative influence was found in the Physical domain. Nevertheless, a positive relation was found between medication use and the Psychological and Social Relations domains of the elderly quilombolas' QoL, which may be related with the positive response the medicine may have provided to these elderly people's health conditions.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…23 The number of medicines negatively influences the Environmental and Physical domains of the studied elderly's QoL and GQoL. These findings are similar to the study 22 in which a negative influence was found in the Physical domain. Nevertheless, a positive relation was found between medication use and the Psychological and Social Relations domains of the elderly quilombolas' QoL, which may be related with the positive response the medicine may have provided to these elderly people's health conditions.…”
Section: Discussionsupporting
confidence: 84%
“…These results are similar to the associated with the Social Relations domain of elderly people's QoL found in another study. 22 In addition, in a study that assessed the QoL of elderly people, it was evidenced that the elderly's background health conditions are one of the factors that most influenced the perceived QoL. 19 The number of main health problems in the elderly was strongly associated with the QoL and GQoL, except for the Psychological domain that, although less intense, interfered negatively in the QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there are reports of an inverse association between the presence of comorbidities and quality of life (13) , a fact corroborated by a systematic review consisted of 30 studies. (21) Nobrega et al, (21) evaluated the association between multimorbidity and quality of life in elderly patients with stable chronic diseases, with a final sample of 104 subjects, and found that with the increasing number of comorbidities, quality of life in sêniors worsened (mainly in the physical, psychological and social aspects). Similar data were also observed by other authors.…”
Section: Discussionmentioning
confidence: 99%
“…According to Nobrega et al, (21) the number of medications used adversely influences the quality of life of patients in the physical domain, and this finding may be possibly related to a higher prevalence of physical inactivity in this population.…”
mentioning
confidence: 81%
“…Scoring system goes like this, 0: no disease; 1(mild): disease with no need for medical attention which does not affect daily activities of patients and good prognosis; 2 (moderate): disease which needs medical attention but no expected complications with good prognosis; 3 (severe): disease which needs urgent medical attention with a bad prognosis; 4 (very severe): disease with a death risk. With each system scored accordingly, CIRS total score varies from 0 to 52 [12].…”
Section: Methodsmentioning
confidence: 99%